A participação dos alunos no projeto de extensão Palestras e Demonstrações Práticas sobre Anatomia Humana - Rodrigues, Giulia Bueno [UNESP]; Bolini, Paulo Domingos André [UNESP]; Gaspar, Ana Maria Minarelli [UNESP]; Gonçalves, Marcela de Almeida [UNESP]; Conte, Marcelo Brito [UNESP]; Capote, Ticiana Sidorenko de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The participation of the students in the Extension Project "Lectures and Practical Demonstration in Human Anatomy" is an extremely rewarding experience. We participate in meetings once a week with the other components of the project and we have been trained by the professors and the coordinator of the project to develop educational materials, as well as we have the opportunity to collaborate with the community through knowledge of the human anatomy. The educational material is developed in the form of Microsoft PowerPoint to present for the target public of the project, which includes Elementary Schools of Elementary and High Schools, the public and private schools of the area of Araraquara and Araraquara city, as well as technical and professionalizing schools, such as nursing, technicians in dental prosthesis, technicians in dental hygiene, dental assistants, civil and military police officers, firefighters, University of the Third Age, etc., totaling about eight hundred people per year. The next meeting of our presentation, we report our experience for the group and in the face of criticism and suggestions made by the professors and colleagues we can improve our next presentation.

A participação dos alunos no Projeto de extensão “Palestras e Demonstrações Práticas sobre Anatomia Humana” é uma experiência extremamente gratificante. Participamos de reuniões semanais com os demais componentes do projeto e somos treinados pelos professores orientadores e pela coordenadora do projeto a desenvolver material didático, além de ter a oportunidade de colaborar com a comunidade passando conhecimentos sobre a Anatomia Humana. O material didático é desenvolvido sob a forma de Microsoft Powerpoint para ser apresentado ao público-alvo do projeto, que abrange Escolas dos ciclos Fundamental e Médio, das redes pública e privada de Araraquara e da região, bem como escolas técnicas e profissionalizantes, como de enfermagem, técnicos em prótese dentária, técnicos em higiene dentária, auxiliares odontológicas, policiais civis e militares, bombeiros, Universidade da Terceira Idade, etc., totalizando cerca de oitocentas pessoas ao ano. Na reunião posterior à nossa apresentação, relatamos nossa experiência para o grupo e diante das críticas e sugestões feitas pelos professores e pelos colegas podemos melhorar nossa próxima apresentação.
Keywords: Anatomy; Education; Extension; Anatomia; Educação; Extensão